1973
DOI: 10.1037/h0034135
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of chimpanzee drawing.

Abstract: Three young chimpanzees were each presented with approximately 100 sheets of paper bearing various stimulus figures and allowed to draw on them. This study differed from earlier ones in using quantitative methods to analyze the drawings obtained. Comparison of the results of this analysis with those obtained from subjective judgments confirmed the importance of such methodological refinements. While some of the conclusions of earlier studies by D. Morris and P. Schiller are confirmed here (e.g., tendencies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
38
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 5 publications
11
38
1
Order By: Relevance
“…Morris's work led to a number of subsequent experiments by others using similar techniques. Later Smith (1973) and Boysen (Boysen et al 1987) confirmed these results, but argued that the pattern resulted from the chimpanzee's placing marks toward the center of the vacant space; balance was an accident. Most chimpanzees presented with a figure that is offset from the center of the paper will mark on the opposite side, or on the figure itself (Fig.…”
Section: What About Apes?mentioning
confidence: 84%
“…Morris's work led to a number of subsequent experiments by others using similar techniques. Later Smith (1973) and Boysen (Boysen et al 1987) confirmed these results, but argued that the pattern resulted from the chimpanzee's placing marks toward the center of the vacant space; balance was an accident. Most chimpanzees presented with a figure that is offset from the center of the paper will mark on the opposite side, or on the figure itself (Fig.…”
Section: What About Apes?mentioning
confidence: 84%
“…Schiller discussed those responses as balancing the composition, ascertaining that Alpha was capable of intuiting a human‐like sense of order. Schiller's studies were followed by Morris (), Smith (), and later, Boysen, Berntson, and Prentice (). Like Schiller, these researchers reported that their chimpanzees marked on the figures or scribbled on blank space; however, they did not observe the balancing behavior observed by Schiller, and thus it appears problematic to claim that chimpanzees possess a sense of order akin to what is likely the origin of human aesthetic sense (Lenain, , ).…”
Section: Drawing Behavior In Chimpanzeesmentioning
confidence: 99%
“…In most cases, drawing occurs spontaneously, that is, without food rewards or special training, and apes will draw or paint as self‐gratifying play (Boysen et al., ; Lenain, ; Matsuzawa, ; Morris, ; Schiller, ; Smith, ; Tanaka, Tomonaga, & Matsuzawa, ). For this reason, drawing opportunities are sometimes proposed as environmental enrichment for great apes in captivity.…”
Section: Drawing Behavior In Chimpanzeesmentioning
confidence: 99%
“…To the contrary, additional experience only seemed to have strengthened the tendency to treat this task associatively, given the relatively small number of trial types and the high number of training trials. This seems to qualify as a "could-learn" type of meaningful failure: Drawing, as operationalized here, is a competency that the rhesus monkeys might reasonably have demonstrated, but it is also possible that the cognitive demands of drawing, which has been demonstrated by apes (e.g., Boysen, Bernston, & Prentice, 1987;Iverson & Matsuzawa, 1996;Smith, 1973) are beyond the abilities of monkeys. What can be concluded at present is that rhesus monkeys have failed to demonstrate the capacity so far to draw in this way.…”
Section: "Could-learn" Failuresmentioning
confidence: 99%